Role of Anabolic Anti-Osteoporosis Therapy in Diabetes Subjects - Harsh Durgia; Rajan Palui; Jayaprakash Sahoo; Sadishkumar Kamalanathan; Dukhabandhu Naik (Indian Journal of Endocrinology and Metabolism)
Diabetes mellitus (DM) is a metabolic disorder that leads to the destruction of various tissues including bones. The pathogenesis of osteoporosis (OP) varies in DM due to many specific factors. DM increases the risk of fracture as well as post-fracture mortality. It is because of this fact that OP treatment should not be neglected in patients with DM. OP therapy comprises anabolic as well as anti-resorptive agents. Primary OP as observed in post-menopausal women is associated with high bone turnover, whereas OP in DM is a disease of low bone turnover. Therefore, anabolic agents seem to be quite promising in cases of OP in DM. Although the anti-fracture efficacy of these drugs is proven beyond any doubt in the general population without DM, evidence in persons with DM is limited. Among the anabolic agents, teriparatide has the most evidence in favor of its efficacy and safety in persons with DM. Studies evaluating other anabolic agents such as abaloparatide and romosozumab in diabetic osteopathy are scarce in the literature. Future studies specifically in both type 1 and type 2 DM populations are needed to evaluate the effects of osteoanabolic agents.